Just-for-Me: An Adaptive Personalization System for Location-Aware Social Music Recommendation - Cheng, Zhiyong (Institutional Knowledge at Singapore Management University, 2014)
In recent years, location-aware music recommendation is increasing in popularity, as more and more users consume music on the move. In this demonstration, we present an intelligent system, called Just-for-Me, to facilitate accurate music recommendation based on where user presents. Our system is developed based on a novel probabilistic generative model, which can effectively integrate the location contexts and global music popularity trends. This approach allows us to gain more comprehensive modeling on user preference and thus significantly enhances the music recommendation performance.